Supervisi Pendidikan Sebagai Upaya Peningkatan Mutu Pendidikan Islam - Fauziah, Fauziah (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2017)
Supervision of Islamic education is required to provide guidance and direction to develop individuals in improving the quality of education together. Islamic values should continue to be taken for the realization of quality education and in line with the demands of the Islamic religion and the curriculum has been set. Therefore, various characteristics possessed by the executor is certainly not the same education that require different handling. Proper supervision pattern will affect the success of the plural in performing tasks relevant and effective education.